Post-traumatic stress disorder, food insecurity, and social capital after the 2017 coastal El Niño flooding among mothers from Piura, Peru: A mixed method study. - Carlos Culquichicón; David Astudillo-Rueda; Roberto Niño-Garcia; Raisa N Martinez-Rivera; Nicole Merino Tsui; Robert H Gilman; Karen Levy; Andrés G Lescano (Public Library of Science (PLoS), 2024)
In order to understand the impacts in the post-disaster scenario of the 2017 El Niño events in the Piura region-Peru, we examined post-traumatic stress disorder (PTSD), food insecurity (FI), and social capital (SC) across three-time points in mothers in highly affected areas. In the Piura, Castilla, and Catacaos districts, we studied mothers combining mixed-method assessments at three (June-July 2017), eight and 12 months after the flooding. Each outcome was measured with the PTSD-Checklist-Civilian (PCL-C), the Household-Food-Insecurity-Access-Scale (HFIAS), the Adapted-Social-Capital-Assessment-Tool (SASCAT) surveys. In-depth interviews at the first evaluation were also conducted. At the first evaluation, 38.1% (n = 21) of 179 mothers reported PTSD; eight months and one year after the flooding, it dropped to 1.9% and virtually zero, respectively. Severe FI also declined over time, from 90.0% three months after the flooding to 31.8% eight months after, to 13.1% one year after. Conversely, high-cognitive SC was increased three months after the flooding (42.1%) and much greater levels at eight and 12 months after (86.7% and 77.7%, respectively). High levels of PTSD and severe FI three months after the flooding consistently decreased to nearly zero one-year post-disaster. High levels of high-cognitive SC may have helped mothers to recover from PTSD and FI in Piura.